1982
DOI: 10.1093/bja/54.9.965
|View full text |Cite
|
Sign up to set email alerts
|

Interaction Between Regional Myocardial Ischaemia and Left Ventricular Performance Under Halothane Anaesthesia *

Abstract: The effect of halothane on the performance of myocardium supplied by a narrowed coronary artery has been assessed in an attempt to examine the influence of halothane on hearts with non-occlusive coronary artery disease. The study was divided into two parts: first, the left anterior descending (LAD) coronary artery was constricted beyond its second diagonal branch and, second, the left circumflex (LC) was constricted close to its origin In both parts, the myocardium was exposed to stepwise increases in inspired… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 25 publications
1
10
0
Order By: Relevance
“…Moreover, in the case of halothane, the greater depression of wall function in the compromised territory was accompanied by the development of abnormal patterns of wall function. These abnormal patterns were similar to those observed in acute myocardial ischaemia (Theroux et al 1976) and were seen when coronary blood flow was severely reduced because of the reduction in arterial pressure (Francis et al 1982). Thus, it appears that anaesthesia may, when myocardial depression occurs, cause severe depression and ischaemic changes in the compromised myocardium.…”
Section: Prevention and Treatment Of Ischaemiasupporting
confidence: 70%
See 1 more Smart Citation
“…Moreover, in the case of halothane, the greater depression of wall function in the compromised territory was accompanied by the development of abnormal patterns of wall function. These abnormal patterns were similar to those observed in acute myocardial ischaemia (Theroux et al 1976) and were seen when coronary blood flow was severely reduced because of the reduction in arterial pressure (Francis et al 1982). Thus, it appears that anaesthesia may, when myocardial depression occurs, cause severe depression and ischaemic changes in the compromised myocardium.…”
Section: Prevention and Treatment Of Ischaemiasupporting
confidence: 70%
“…Recently, the effects of halothane , 1981, Francis et al 1982) and enflurane (Cutfield et al 1980) on global and regional cardiac function have been studied in dogs in which a coronary artery had been critically narrowed. With critical constriction, autoregulation of coronary blood flow is lost and there is no coronary flow reserve.…”
Section: Prevention and Treatment Of Ischaemiamentioning
confidence: 99%
“…Experimental and clinical studies with different volatile agents have also proved inconclusive. Data from studies with halothane have suggested that it may be a useful volatile supplement for patients with ischaemic heart disease, although this is controversial [2,19]. The use of isoflurane has provoked considerable controversy.…”
Section: Fig 5 Changes In Mean (Se) Values Of Coronary Sinus and Greatmentioning
confidence: 99%
“…Of the anaesthetic agents in common use halothane [2], enflurane [3]. fentanyl and its derivatives [4][5][6], nitrous oxide [7] and isoflurane [8] have all at some time been associated with either haemodynamic effects likely to promote myocardial oxygen imbalance, experimental evidence of ventricular wall motion abnormality, or direct metabolic or electrophysiological evidence of anaerobic cardiac metabolism.…”
mentioning
confidence: 99%
“…Experimental studies using acute coronary occlusions have shown that halothane (55), enflurane (56) and morphine (57,58) minimize the signs of ischaemia and reduce the size of myocardial infarction after coronary occlusion (58,59). However, more recent studies using a model of critical constriction rather than occlusion of a coronary artery have shown that halothane and enflurane cause more depression of an area of the myocardium supplied by a narrowed coronary artery than of an area with a normal blood supply (60,61,62). In the case of halothane, abnormal patterns of wall function were observed and appeared to indicate that the compromised segment was becoming ischaernic (60, 61).…”
Section: Protection Of the Ischaemic Myocardiummentioning
confidence: 99%